The Calcineurin Inhibitor Tacrolimus Specifically Suppresses Human T Follicular Helper Cells - Wallin, Elizabeth F.; Hill, Danika L.; Linterman, Michelle A.; Wood, Kathryn J. (Frontiers in Immunology, 2018)
Background: T follicular helper (Tfh) cells are key players in the production of antibody producing B cells via the germinal centre reaction. Therapeutic strategies targeting Tfh cells are important where antibody formation is implicated in disease, such as transplant rejection and autoimmune diseases. We investigated the impact of the immunosuppressive agent tacrolimus on human Tfh cell differentiation and function in transplant recipients. Methods: Paired blood and lymph node (LN) samples were obtained from 61 transplant recipients immediately prior to organ implantation. Living-donor recipients received a week of tacrolimus prior to kidney transplantation. Deceased-donor recipients served as controls, as tacrolimus was not administered until after the transplant operation. Flow cytometry was used to compare LN and circulating cell subsets. Results: The calcineurin inhibitor tacrolimus specifically suppresses both LN Tfh cells and circulating Tfh cells, but not their regulatory counterparts or other CD4 T cell subsets. Conclusions: Our findings suggest that calcineurin inhibitors may have a more important role in the prevention of antibody formation than previously understood and therefore have potential for antibody-associated conditions in which aberrant Tfh function has been implicated in disease.